2017
DOI: 10.1186/s12879-017-2685-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for Staphylococcus aureus nasopharyngeal carriage during a PCV trial

Abstract: BackgroundWe conducted an ancillary study among individuals who had participated in a cluster-randomized PCV-7 trial in rural Gambia (some clusters were wholly-vaccinated while in others only young children had been vaccinated), to determine the prevalence and risk factors for Staphylococcus aureus nasopharyngeal carriage.MethodsTwo hundred thirty-two children aged 5–10 years were recruited and followed from 4 to 20 months after vaccination started. We collected 1264 nasopharyngeal swabs (NPS). S. aureus was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The overall S. aureus nasopharyngeal carriage prevalence of 23.2% is comparable to what has been reported previously in Ghana in the nasopharynx of HIV-infected children below five years of age (22.03%) [12] and in the anterior nares of the general population (21%) [54] and children with sickle cell disease (33.3%) [14], but it is heterogeneously lower (44.9%) [13] and higher (8%) [55] than the prevalence among HIV-infected patients post-PCV introduction. It is also comparable to what has been reported for nasopharyngeal carriage in other countries: in The Gambia (20-25.9%) [56,57], Portugal (21.6%) [58], and the Netherlands (23.2%) [25]. However, the post-vaccination carriage prevalence recorded among apparently healthy children in the current study is slightly lower than what was reported in Iran (29.6%) [59], Belgium (34%) [60], Vietnam (30.6%) [61], and The Gambia (30.6%) [62], but higher than that reported in Ethiopia (10.3%) [3].…”
Section: Discussionsupporting
confidence: 89%
“…The overall S. aureus nasopharyngeal carriage prevalence of 23.2% is comparable to what has been reported previously in Ghana in the nasopharynx of HIV-infected children below five years of age (22.03%) [12] and in the anterior nares of the general population (21%) [54] and children with sickle cell disease (33.3%) [14], but it is heterogeneously lower (44.9%) [13] and higher (8%) [55] than the prevalence among HIV-infected patients post-PCV introduction. It is also comparable to what has been reported for nasopharyngeal carriage in other countries: in The Gambia (20-25.9%) [56,57], Portugal (21.6%) [58], and the Netherlands (23.2%) [25]. However, the post-vaccination carriage prevalence recorded among apparently healthy children in the current study is slightly lower than what was reported in Iran (29.6%) [59], Belgium (34%) [60], Vietnam (30.6%) [61], and The Gambia (30.6%) [62], but higher than that reported in Ethiopia (10.3%) [3].…”
Section: Discussionsupporting
confidence: 89%
“…We found S. aureus bacteremia to be more common during the wet season. This seasonal variation might relate to S. aureus colonization (a prerequisite for disease), which is highest during the wet season ( 31 ), or seasonal differences in the incidence of viral infections, which are known to disrupt mucosal epithelium, thereby encouraging S. aureus invasion ( 32 ). In a study of US adults ( 33 ), the peak incidence of S. aureus infection occurred during the winter months and coincided with the peak incidence of viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Gambian children had an S. aureus carriage increase 4 months after PCV-7. 47 In South Africa, children had an initial increase in S. aureus carriage post-PCV-7 immunization that then normalized 16 months post-immunization. 33 It is difficult to make comparisons with other studies as they differ in age, size, methodology, immunization doses, and the time point postimmunization.…”
mentioning
confidence: 99%